Enhancing Awareness and Community Participation in Sigi Village for Effective and Sustainable Development - Rizki Masyahbandi; Lita Liani; Elsya Marlina; Gio Hermawan; Jessika R. Silaban; Davie Surya rayoga; Rafly Hermawan; Yoga Agustiawan; Indra Siregar; Octa Adriano; Amara; Samuel Kristofani S (Bratasena: Jurnal Pengabdian Kepada Masyarakat, 2026)
Background: Many community members remain insufficiently active in participating in various development processes and village-level decision-making. Contribution: Applying community empowerment knowledge acquired during academic studies through concrete activities within the community. Method: The method used in delivering the socialization material employed a direct and interactive approach. The material was presented face-to-face by the resource person to the Village Head as well as the village administrative staff. Results: The outcome of this socialization activity was an increase in awareness and the practice of community participation in inclusive and democratic village decision-making, which was fully supported by the Village Head as a facilitator and leader of village deliberations. Conclusion: The evaluation of the implementation of the socialization activity indicates that the program was carried out effectively and generally received positive responses from the village head and the supporting staff.